Evaluating central mechanisms for age-related force control deficits of the legs - Hanson, Moriah R., author; Fling, Brett W., advisor; Broussard, Josiane, committee member; Stephens, Jaclyn, committee member (Colorado State University. Libraries, 2019)
Advancing age is accompanied by several motor control impairments, including increased movement and force variability. Specifically, older adults display more variable and less accurate submaximal forces than young adults, which have been associated with fall risk in the aged population. These motor control changes take place in muscles in both the upper and lower limbs, and the mechanisms of these alterations are multifactorial, including sources in the peripheral and central nervous systems. Furthermore, inhibitory signaling in the motor cortex is related to force variability in small hand muscles, as well as to coordination of the legs during walking. It is unknown, however, whether inhibition is associated with force variability in the legs. Therefore, the purpose of this study was to assess the relationship between motor cortex inhibition and force variability in the quadriceps muscles of young and old adults. We measured quadriceps force variability and accuracy during a 2-minute force matching task and inhibition via the cortical silent period in 14 young and 15 old adults. Older adults produced more variable and less accurate forces than the young adults, though these differences were not significant. Additionally, older adults displayed less inhibition in their right cortical hemisphere than young adults, as well as interhemispheric inhibitory differences. Specifically, the left hemisphere displayed more inhibition than the right hemisphere in old adults. Furthermore, young adults with more inhibition generally produced more variable and less accurate forces than young adults with less inhibition, while older adults with more inhibition displayed less variable and more accurate forces. The between- and within-group differences in inhibition may point to age-related decline in right hemispheric function. Moreover, between-group differences in inhibition and force variability associations indicate a shift in the inhibitory control of movement, which is a similar finding to previous work on inhibition and lower limb coordination.